Some words of thieves jargon from the 16th century (gloss to the articles of Witold Maisl [1956] and Bogdan Walczak [1993]) - Pacuła, Jarosław (Papers in Linguistics, 2021)
This text concerns the history of the Polish thief sociolect. The article is a commentary on two texts: the text of Witold Maisl (a historian of law), who in 1956 in “Język Polski” shared with the linguistic community discovered in the Poznań archives a small collection of Old Polish vocabulary, and the article is a commentary on the study of Bogdan Walczak (linguist), who in 1993 in the “Kronika Miasta Poznania” commented on the material presented by Maisl. Linguistic remarks leave one unsatisfied and the comment needs to be corrected and supplemented. This article provides an in-depth historical-language analysis of words from a 16th-century court document. The author presents in it the real sources of some old terms along with the probable provenance of some lexemes. There are hypotheses in the article, so this text can be an excuse for further linguistic discussion.